Implementasi Media Grafik Nada dengan Kendali Remote Control untuk Meningkatkan Keterampilan Membaca Notasi Angka pada Siswa Sekolah Dasar - Handayani, Tri (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objectives were to improve the pupils’ skill in note reading through graphic media with remote control and to identify the media’s strength at the elementary school. The media were designed with recycled remote control materials which would ease them in rolling note graphic paper in a distance. This research was designed using as a classroom research. The subjects were recruited from the fourth graders at the public elementary school 2 at Rejang Lebong. The results show the graphic media with remote control could improve the pupils’ understanding of low, medium and high tones. The media could also assist the pupils’ creativity, independence, and understanding of new songs. The pupils’ success exceeded the minimum mastery level after the implementation of note graphic media with recycled remote control.